PENGARUH GAYA HIDUP, E-WOM, DAN KUALITAS PRODUK TERHADAP MINAT BELI PRODUK SEPATU SNEAKER NEW BALANCE - Herdiansyah, (2023)
The Sneakers have evolved into a cultural phenomenon, encompassing fashion, sports, and self-expression. New Balance, as one of the players in the industry, has experienced significant growth in recent years by aligning its products more closely with the primary consumer base of sneakers, namely the younger generation. The study aimed to analyze and examine the influence of Lifestyle, E-WOM, and Product Quality on the Purchase Intention of New Balance sneaker products. A quantitative research approach was adopted, and data were collected through a questionnaire distributed to 100 respondents who were users of sneaker products. The data collection utilized a Google form questionnaire with purposive sampling, and the analysis was conducted using SmartPLS and the three-box method. The findings of the study revealed that (1) Lifestyle had a significant and positive impact on the Purchase Intention of New Balance sneaker products. Similarly, (2) E-WOM was found to have a significant and positive influence on Purchase Intention. Additionally, (3) Product Quality was found to significantly and positively affect Purchase Intention.